How to grill vegetables : the new bible for barbecuing vegetables over live fire - Raichlen, Steven (Workman Publishing, 2021)
"America's grilling guru offers a primer for how to grill vegetables - with lots of creative flavors and techniques - whether you're eating main dishes that highlight vegetables, or you're rounding out the barbecue menu with grilled garden-fresh sides. Not a vegetarian book, but vegetable-forward (and with vegetarian and vegan adaptations)"--